Noncoding DNA, isochores and gene expression: nucleosome formation potential - Vinogradov, Alexander E. (Oxford University Press, 2005)
The nucleosome formation potential of introns, intergenic spacers and exons of human genes is shown here to negatively correlate with among-tissues breadth of gene expression. The nucleosome formation potential is also found to negatively correlate with the GC content of genomic sequences; the slope of regression line is steeper in exons compared with noncoding DNA (introns and intergenic spacers). The correlation with GC content is independent of sequence length; in turn, the nucleosome formation potential of introns and intergenic spacers positively (albeit weakly) correlates with sequence length independently of GC content. These findings help explain the functional significance of the isochores (regions differing in GC content) in the human genome as a result of optimization of genomic structure for epigenetic complexity and support the notion that noncoding DNA is important for orderly chromatin condensation and chromatin-mediated suppression of tissue-specific genes.